Przegląd koncepcji pomiaru regionalnej innowacyjności w unijnej statystyce - Strahl, Danuta; Markowska, Małgorzata (The review of regional innovativeness measurement concepts in the EU's statistics, 2006)
In the years to come the EU’s prospects for development will be defined by competitive capacities of particular countries and regions, including innovativeness as a strategic factor. Stimulating towards taking up innovative activities is a key condition of the Lisbon Strategy – the objective is to achieve a situation in which the European Union would become the most competitive, vigorously developing and based on knowledge economy, till the end of the current decade. In order to upgrade the standard of life in the nearest future the European Union should take over the role of the world leader in the field of innovations. The article presents the European Union’s experiences in research and measurement of regional innovativeness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 49-61